TINDAK TUTUR DIREKTIF DALAM PENGAJARAN PERCAKAPAN BAHASA INGGRIS (Studi Kasus Pengajaran Percakapan Bahasa Inggris pada Mahasiswa Semester 1 di LP3I Yogyakarta) - , ATIN KURNIAWATI; , Prof. Dr. I Dewa Putu Wijana, S.U., M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study is about directive speech acts in English conversation teaching. The purposes of this study are to describe the types of directive speech acts in English conversation teaching, describe delivery strategies of directive speech acts in English conversation teaching, describe functions of directive speech acts in English conversation teaching, and describe politeness strategies of directive speech acts in English conversation teaching. This is a qualitative descriptive study. The data of this study were directive speech acts spoken by English conversation teacher in LP3I Yogyakarta during the class sessions. The data were collected by using observation method and involved observation techniques. The data were recorded and transcribed. Then, the data were categorized. The data were analyzed by using contextual method with pragmatic approach. The result of data analysis was presented informally. Based on the results of the data analysis, there were various types, delivery strategies, functions, and politeness strategies of directive speech acts in English conversation teaching. The types of directive speech acts in English conversation teaching were command, invitation, request, permission, satire, elicitation, advice, suggestion, please, prohibition, warning, and complaint. Command speech act was commonly found. Directive speech acts delivery strategies in English conversation teaching consists of literal direct strategy, nonliteral direct strategy, literal indirect strategy, and nonliteral indirect strategy. Literal indirect speech acts were the most frequently used. Directive speech act functions in English conversation teaching were commanding, requesting, forbidding, giving permission, entrusting, teasing, reminding, inviting, asking for information, advising, suggesting, motivating, pleasing, encouraging, and improving studentâs activeness. The directive speech act function that was often used by the teacher was commanding. In delivering directive speech acts, the teacher used politeness strategies i.e speak directly without face saving act and speak with face saving act with positive and negative politeness strategies .